MANAGEMENT OF PEDIATRIC RHEUMATOLOGICAL DISEASES DURING THE OUTBREAK OF COVID-19: OUR EXPERIENCE - Romina Gallizzi; Diana Sutera; Francesca Mazza; Alessandra Spagnolo; Giovanni Battista Pajno (Mediterranean Journal of Hematology and Infectious Diseases)
Since the COVID-19 epidemic has evolved rapidly also in Italy, specialists in pediatric rheumatology have found themselves addressing the problems of their patients and in particular how to manage the risk of infection and immunosuppressive treatment. This work aims to make known the experience of our center.